Service-learning Programs for Romanian Students – An Analysis of the International Programs and Ideas of Implementation - Rusu, Alina Simona; Bencic, Aurora; Hodor, Teodor Ioan (Procedia, social and behavioral sciences, 2014)
One of the most common definitions of Service-Learning (S-L) programs refers to the use of community-based projects to supplement traditional curricula of the students and to enrich “by doing” the subjects covered in the teaching environment. The aim of this paper is to present a review of the international S-L programs in higher education system (European and international Universities) and to analyze those ideas that could be implemented in Romania. While in most of the SL international programs, the agents involved in the delivery of the SL programs are the teachers, we will especially discuss those SL programs in which the agents are not the teachers, but specific categories of students. Specifically, we performed a case study of the Faculty of Psychology and Sciences of Education (“Babes-Bolyai” University, Romania), which, since 1992, has one of the most active Student Associations in Romania, i.e. Romanian Association of Psychology Students (RAPS). Also, the Faculty has several successful distance learning programs in Psychology, Special Education and Pedagogy. Thus, the Faculty has these two student-based categories of driving forces in terms of offering themselves SL activities: (1) a very active Association of students and (2) a large number of mature students from the distance learning study programs – most of these students are currently employed and/or have graduated another Faculty (some of them are also holders of PhD titles). Based on the literature review, we discuss here the possibilities to include these two categories of students in the Quality Assurance program of the Faculty, in terms of establishing their role as active agents of the QA process. These strategies should be based on the facts that: (1) the members of the Student Association have the potential to develop themselves as a culture with standards and values in the area QA at Faculty level, and (2) the category of mature (adult) students could bring, in a structured manner, an important insight to the other types of students at levels of career orientation, work-related expectations and humane-abilities development. Most important, the ideas of S-L programs implementation are analyzed from the perspective of internalization strategies of the European standards for internal quality assurance within Romanian higher education system.